Floating primary polyps of Nemopilema nomurai on detritus: effects of abiotic factors on their resettlement and subsequent growth - Feng, Song; Xu, Xueting; Mo, Shiyu; Xu, Yaran; Lin, Jianing; Wang, Xiaodong; Jia, Xiaobo; Sun, Song (Frontiers in Ecology and Evolution, 2025)
Studies on the formation process and physio-ecological characteristics of primary polyps would help understand the causes of giant jellyfish Nemopilema nomurai blooms in the coastal sea of East Asia. A new mode of settlement and metamorphosis from planulae into primary polyps was observed in this study by artificially breeding N. nomurai polyps in a large tank. N. nomurai planulae could successfully metamorphose into primary polyps with ≤4 tentacles in the seawater, even though they did not initially colonize the hard substrates as previously reported. The developed primary polyps were then able to hang upside down on detritus via the mucus secreted by planulae and float on the seawater surface. Their resettlement on the large, hard substrates showed significant preference to plastic materials (e.g., polyethylene plates); however, the resettlement density was significantly reduced owing to the increase of age. The resettlement of primary polyps was also affected by the combination of salinity and age. The survival of primary polyps increased, but their resettlement percentage significantly decreased at hyposalinity of 10–23 and older age. This study also found that primary polyps on the detritus could normally develop into individuals with 16 tentacles. There was no significant difference in their survival, development of 14–16 tentacles, and calyx growth at salinities of 15–33, indicating their euryhalinity adaptability. This study suggested that floating in the seawater by attaching to detritus was a possible living mode of N. nomurai polyps inhabiting the estuaries’ surroundings, which may favor polyp population recruitment and maintenance.